Time frame of 753–680 Ma juvenile accretion during the São Gabriel orogeny, southern Brazilian Shield - Hartmann, L.; Philipp, R.; Santos, J.; McNaughton, Neal (Elsevier Science BV, 2011)
The time frame of the three main geological events in the Neoproterozoic Cambaí Complex, juvenile São Gabriel belt in the southern Brazilian Shield is established by integrating field mapping, back-scattered electron imaging and sensitive high-resolution ion microprobe (SHRIMP II) U–Pb dating of 96 zircon crystals from nine granitic and metasedimentary rock samples. The three events are: (1) voluminous flat-lying paragneisses (Cambaizinho Complex) and orthogneisses (Vila Nova gneisses) between 735 and 718 Ma, (2) tonalite–trondhjemite association (Lagoa da Meia-Lua Suite) between 710 and 690 Ma, and (3) late granodiorite intrusions (Sanga do Jobim Suite) at 680 Ma. An additional older volcanic event (Campestre Formation) was dated at 753 Ma. These results are most significant for the reconstruction of West Gondwana.